Steady‐state and synchronous spectrofluorimetric methods for simultaneous determination of aliskiren hemifumarate and amlodipine besylate in dosage forms. (31st March 2014) - Ebeid, Walid M.; Elkady, Ehab F.; El‐Zaher, Asmaa A.; El‐Bagary, Ramzia I.; Patonay, Gabor
ABSTRACT Aliskiren hemifumarate (ALS) and amlodipine besylate (AML) were simultaneously determined by two different spectrofluorimetric techniques. The first technique depends on direct measurement of the steady‐state fluorescence intensities of ALS and AML at 313 nm and 452 nm upon excitation at 290 and 375 nm, respectively, in a solvent composed of methanol and water (10: 90, v/v) . The second technique utilizes synchronous fluorimetric quantitative screening of the emission spectra of ALS and AML at 272 and 366 nm, respectively using Δλ of 97 nm. Effects of different solvents and surfactants on relative fluorescence intensity were studied. The method was validated according to ICH guidelines. Linearity, accuracy and precision were found to be satisfactory in both techniques over the concentration ranges of 1–15 and 0.4–4 µg/mL for ALS and AML, respectively. In the first technique, limit of detection and limit of quantification were estimated and found to be 0.256 and 0.776 µg/mL for ALS as well as 0.067 and 0.204 µg/mL for AML, respectively. Also, limit of detection and limit of quantification were calculated in the synchronous method and found to be 0.293 and 0.887 µg/mL for ALS as well as 0.034 and 0.103 µg/mL for AML, respectively. The methods were successfully applied for the determination of the two drugs in their co‐formulated tablets. The results were compared statistically with reference methods and no significant difference was found. The developed methods are rapid, sensitive, inexpensive and accurate for the quality control and routine analysis of the cited drugs in bulk and in pharmaceutical preparations without pre‐separation. Copyright © 2014 John Wiley & Sons, Ltd.